Land Cover and Coast Line Change Detection by Using Object Oriented Image Processing in Alacati, Turkey - Gucluer, Dolunay; Bayram, Bulent; Maktav, Derya (IOS PRESS, 2010)
The chosen study area Alacati is one of the most significant tourist regions in Turkey. Due to its natural and geographical characteristics it faces different threats, such as coastline changes by moving solid matter or formation of filled areas caused by anthropogenic effects. The detection of the coastline and land cover changes in Alacati has been investigated by using multitemporal satellite images, such as CORONA of 1963, LANDSAT of 1987 and 2000, and ASTER of 2007. Object oriented remote sensing software was used. This software is preferred due to its capability of generating fuzzy segmentation and classification by using both texture and reflection attributes of images and also for different types of data. Thus, the purpose of this study was to establish a basis for planning of preventing Alacati region.
Keywords: Coastline; Alacati; Object oriented classification; CORONA; LANDSAT; ASTER; Remote Sensing